Map-1a regulates Sertoli cell BTB dynamics through the cytoskeletal organization of microtubule and F-actin - Lingling Wang; Ming Yan; Tiao Bu; Xiaolong Wu; Linxi Li; Bruno Silvestrini; Fei Sun; C. Yan Cheng; Hao Chen (BMC, 2024)
Abstract Microtubule-associated protein 1a (Map1a) is a microtubule (MT) regulatory protein that binds to the MT protofilaments in mammalian cells to promote MT stabilization. Maps work with MT cleavage proteins and other MT catastrophe-inducing proteins to confer MT dynamics to support changes in the Sertoli cell shape to sustain spermatogenesis. However, no functional studies are found in the literature to probe its role in spermatogenesis. Using an RNAi approach, coupled with the use of toxicant-induced testis (in vivo)- and Sertoli cell (in vitro)-injury models, RNA-Seq analysis, transcriptome profiling, and relevant bioinformatics analysis, immunofluorescence analysis, and pertinent biochemical assays for cytoskeletal organization, we have delineated the functional role of Map1a in Sertoli cells and testes. Map1a was shown to support MT structural organization, and its knockdown (KD) also perturbed the structural organization of actin, vimentin, and septin cytoskeletons as these cytoskeletons are intimately related, working in concert to support spermatogenesis. More importantly, cadmium-induced Sertoli cell injury that perturbed the MT structural organization across the cell cytoplasm was associated with disruptive changes in the distribution of Map1a and a surge in p-p38-MAPK (phosphorylated p38-mitogen-activated protein kinase) expression but not total p38-MAPK. These findings thus support the notion that p-p38-MAPK activation is involved in cadmium-induced Sertoli cell injury. This conclusion was supported by studies using doramapimod, a specific p38-MAPK phosphorylation (activation) inhibitor, which was capable of restoring the cadmium-induced disruptive structural organization of MTs across the Sertoli cell cytoplasm. In summary: this study provides mechanistic insights regarding restoration of toxicant-induced Sertoli cell and testis injury and male infertility.